2011
DOI: 10.1371/journal.pone.0020535
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Chimeric Dual-Chain Avidin by Tandem Fusion of the Related Avidins

Abstract: BackgroundAvidin is a chicken egg-white protein with high affinity to vitamin H, also known as D-biotin. Many applications in life science research are based on this strong interaction. Avidin is a homotetrameric protein, which promotes its modification to symmetrical entities. Dual-chain avidin, a genetically engineered avidin form, has two circularly permuted chicken avidin monomers that are tandem-fused into one polypeptide chain. This form of avidin enables independent modification of the two domains, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Avidin is a frequently utilized protein tool in a plethora of life science applications, including imaging, purification, labeling, targeting, and detection. , This chicken-derived tetrameric beta-barrel protein has many desirable properties: it is rather small in size (60 kDa), it can be efficiently produced in E. coli , its structure is well-known (e.g., [PDB: 1VYO]), and it is highly resistant to a wide range of denaturing conditions such as high temperatures, extreme pH values, and many organic solvents. , Furthermore, its structure–function relationship has been widely explored using rational mutagenesis, and several avidins with tailored and novel functions exist, such as dual-chain avidin, single-chain avidin, extremely thermostable avidin, , and steroid-binding avidin, thus expanding even further the usability of this scaffold.…”
mentioning
confidence: 99%
“…Avidin is a frequently utilized protein tool in a plethora of life science applications, including imaging, purification, labeling, targeting, and detection. , This chicken-derived tetrameric beta-barrel protein has many desirable properties: it is rather small in size (60 kDa), it can be efficiently produced in E. coli , its structure is well-known (e.g., [PDB: 1VYO]), and it is highly resistant to a wide range of denaturing conditions such as high temperatures, extreme pH values, and many organic solvents. , Furthermore, its structure–function relationship has been widely explored using rational mutagenesis, and several avidins with tailored and novel functions exist, such as dual-chain avidin, single-chain avidin, extremely thermostable avidin, , and steroid-binding avidin, thus expanding even further the usability of this scaffold.…”
mentioning
confidence: 99%
“…The binding site of Avds has been engineered by both mutating single residues involved directly in biotin binding and by manipulating the loop regions of Avds important for ligand recognition and specificity [37,38]. The L3,4-loop in particular, with a vital role for biotin binding, has been an active target for mutagenesis [5,710]. In our recent study, we reported antidins, i .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several modifications aiming to alter avidin–biotin binding properties have been introduced . For example, reversible systems with monomeric and whole avidins have been developed to allow for regeneration of the respective biointerface. Bifunctional avidins with two different biotin binding pockets , and that bind covalently to biotin have been reported, and the thermal stability (denaturation temperature over 90°) of avidin has been improved via chemical modification …”
Section: Introductionmentioning
confidence: 99%